The correlation between economic fluctuation, workforce employment and health expenditure in the BRICS countries - Gu, Lingyan; Wang, Mei-Chih; Li, Fangjhy (Frontiers in Public Health, 2022)
In this paper, we use economic fluctuations and employment rates in BRICS countries to examine the impact on health expenditures. We used the Bootstrap ARDL method, data from 2000 to 2018, to test whether correlations between economic fluctuations, health care expenditures, and employment rates among the BRICS countries were found. In our study shows that in the long-term, there is no cointegration relationship between these three variables except South Africa. In the short-term Granger causality test, economic fluctuations in Brazil, China, and South Africa have a significant impact on health care costs by a lag one-period of time. Economic fluctuations in Brazil, India, and China have a negative impact on employment rates, while South Africa has a positive impact. Health expenditures in Russia and India have a negative impact on employment rates, while China has a positive impact. Employment rates in China and South Africa have a significant positive impact on economic fluctuations, while Russia has a negative impact. Employment rates in India have a negative impact on health expenditures, and South Africa has a positive impact. In the short-term causality test, different countries will show different phenomena. Except for economic fluctuations, health expenditure is positive, but it is not important. Others are negative causality, and South Africa is all positive causality.